Distribution and sources of macrolitter on the seafloor in Belgian fisheries areas - David Vanavermaete; Katrien Verlé; Lisa I. Devriese; Karien De Cauwer; Coline De Schrijver; Els Torreele; Loes Vandecasteele; Milica Velimirovic; Kristof Tirez; Kris Hostens; Bavo De Witte (Frontiers in Marine Science, 2023)
Marine litter is recognized as a global environmental concern. Seafloor litter can provide important information to help assess the status of the marine ecosystem and is relatively easy to collect on a regular basis. The Belgian fisheries area covers different parts of the OSPAR Greater North Sea region and the Celtic Seas. In these regions, seafloor litter data were gathered by quantifying the litter items caught in the trawl net during two different fisheries surveys to investigate litter distribution on both regional and local scales. In the international beam trawl survey (BTS), covering essentially the OSPAR Greater North Sea and Celtic Seas, an average of 2.2 ± 0.05 items.ha -1 were caught with a median of 1.4 items.ha -1 . In the environmental monitoring survey (EMS) only the Belgian part of the North Sea was covered and a smaller cod-end mesh size was used, resulting in 12.7 ± 1.7 litter items.ha -1 in the coastal zone (< 12 nm) and 2.8 ± 0.2 items.ha -1 in the more offshore zone (> 12 nm). In both surveys plastic items were predominant, representing up to 88% of the collected litter in the Belgian part of the North Sea. The impact of human activities at sea such as fisheries, sand extraction, wind farms and dredge disposal was investigated. A significant correlation was found between fishing activities and the amount of litter registered in the Belgian part of the North Sea, but not for the OSPAR Greater North Sea and Celtic Seas.